A systematic revision of the deep-sea subfamiliy lipomerinae of the isopod crustacean family Munnopsidae - Wilson, George D. F. (Berkeley, California University of California Press, 1989)
Bulletin of the Scripps Institution of Oceanography University of California, San Diego; v.27
Keywords: Crustacea--Classification.; Munnopsidae--Classification.